PERLINDUNGAN HAM BAGI TENAGA KERJA DISABILITAS PADA PT PERTAMINA REFINERY UNIT V BALIKPAPAN - Putri, Wahyuning Utami; Madalina, Maria (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This legal research aims to find out the configuration of human right protection for disability workers conducted at PT Pertamina Refinery Unit V Balikpapan and what are the constraints faced by the companies in providing protection to disability workers. This writing is a legal research based on empirical or non-doctrinal research in order to discover the real circumstances occurred on the research sites.The research uses primary data in the form of observation and interview, as well as secondary data in the form of Act No. 8 of 2016 on Disability, Act No. 13 of 2003 on Employment and Government Ordinance No. 43 of 1998 on Disability Welfare Efforts. The data was collected by library research of legal material relating to the research and data obtained from field observations and interviews to the Employment Section Head and to the disability workers in PT Pertamina Refinery Unit V Balikpapan. The results show 4 (four) kinds of conclusions. Firstly, the protection of disability workers is already running but have not been optimal yet. The disability workers have been granted the rights under applicable law. Secondly, PT Pertamina Refinery Unit V Balikpapan has not fulfilled the obligation to employ disability workers at least 2% of the total workers owned by the company. Thirdly, PT Pertamina Refinery Unit V Balikpapan also has not provide disabled facilities to disability workers. Last, the obstacles faced by PT Pertamina Refinery Unit V Balikpapan in providing protection to disability workers due to the absence of regulation from PT. Pertamina in applying laws and the lack of government socialization and supervision in the implementation of the law as well as lack of public understanding of the rights that should obtained by People with Disabilities (PwDs).